The ‘crimen maiestatis’ between the 1st century BC and the 1st century AD: some comparative points - Lanna de Freitas, João Victor (Romanitas - Revista de Estudos Grecolatinos, 2022)
The central subject of this paper is to analyze the increase of incidence and representativeness of crimen maiestatis populi romani imminutae trials and charges comparing the classic literature about the I BC and I AD centuries. Considering this, the main question is why this crime was represented by the sources that wrote about the Julio-Claudian dynasty with a higher frequency than narratives about Republican times. In the other words how the crimen maiestatis becoming the favourite of the delators, when, less than one Century before it had been described by Cicero as a complicated field (Cic. Clue. 116, 6-7), that was rarely treated by the juristic manuals (Cic. De Or. 2. 201, 2)? To answer these questions, a wide number of literary documents were studied. The analyze of these historical documents tries to show how a set of political, rhetorical and legal elements could impacted in the frequency and way the maiestas prosecutions was represented in the narratives about the period between Augustus and Nero.
Keywords: Late Republic; Roman Principate; Crimen maiestatis; Ancient narratives